Comment on Project THANKS: Examining HIV/AIDS-Related Barriers and Facilitators to Care in African American Women: A Community Perspective. (14th August 2020) - Amutah-Onukagha, Ndidiamaka; Mahadevan, Meena; Opara, Ijeoma; Rodriguez, Monica; Baxter, Aminah; Trusdell, Megan; Kelly, Jessica
The aim of Project THANKS (Turning HIV/AIDS into Knowledge for Sisters) was to provide resources for African American women living with a dual diagnosis of HIV and associated comorbidities such as a chronic illness, and substance use disorder. HIV self-management is viewed within a larger context that addresses HIV and comorbidities concurrently. Project THANKS is an evidence-based, culturally competent curriculum that provides African American women with the necessary knowledge and tools to manage their complications associated with having multiple chronic diseases. The intervention was piloted in 2015 and later conducted in 2018 in 3 community-based health centers in New Jersey. Future interventions of Project THANKS will address the social support, mental health, and health literacy needs expressed by participants as well as incorporating a licensed social worker to further improve their physical and mental health outcomes.